1910 S.C. Acts 694, no. 859, § 1. - (:unkn) unknown (My University, 1910)
That from and after the approval of this Act it shall be unlawful for any person to present or point at any other person any loaded or unloaded firearm, and any one, on conviction therefor, shall be punished by fine or imprisonment, in the discretion of the court; provided that nothing contained herein shall be construed to abridge the right of self-defense or to apply to theatricals or like performances.
Keywords: BRANDISHING